Management of Digital-Based Mail Product System at The East Barito State Attorney’s Office - Ritawaty, Noor; Dasmasela, Viddy; Kumala, Anastasia Greta; Wahyuno, Fiktory; Syalehenor, Syalehenor (Journal Research of Social Science, Economics, and Management, 2024)
Today’s technological developments are in accordance with the demands of Bureaucratic Reform, where every work unit must change work patterns, namely from conventional work patterns to technology-based work patterns, if previously the performance and postal posts to carry out office administration were carried out manually at this time must be done digitally. The object of this research is the East Barito State Prosecutor’s Office in Tamiang Layang. Where the implementation of mail administration has run 85% with an electronic / digital system that is accommodated in the SIPEDE Application (Electronic Mail Information and Disposition System). The performance implementation system and the application of digital mail administration is the implementation of changes in performance weights that were previously physical, but now the presentation of data is virtual and online, this is an advancement in information technology. The research methods used are interviews, observations, documentation, and literature studies. The result of this study is that the waterfall method is a system method and the blackbox method is a system and questionnaire testing method. Programming languages namely PHP (hypertext Preprocessor) and MySQL as database management, then as implementers, of course, qualified human resources are needed and have IT expertise (Computer Institutions) for the implementation and successful use of the technology in question.